2013
DOI: 10.1111/jcpp.12107
|View full text |Cite
|
Sign up to set email alerts
|

Parental separation/divorce in childhood and partnership outcomes at age 30

Abstract: These findings suggest that the general associations between childhood parental separation/divorce and partner relationships in adulthood reflect the consequences of various contextual factors that are associated with childhood parental separation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 45 publications
(70 reference statements)
0
23
0
2
Order By: Relevance
“…Some studies have found that after extensive control of covariates, the direct link between exposure to parental separation and later outcomes is reduced altogether (e.g. Fergusson, McLeod, & Horwood, ). Due to the overlap in the timing of these life‐course events with the timing of exposure to parental separation, it was not possible to test specific mediational pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found that after extensive control of covariates, the direct link between exposure to parental separation and later outcomes is reduced altogether (e.g. Fergusson, McLeod, & Horwood, ). Due to the overlap in the timing of these life‐course events with the timing of exposure to parental separation, it was not possible to test specific mediational pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Partiendo de nuestros resultados, se observa una clara relación significativa entre problemas en el ámbito familiar durante la infancia como factor de riesgo asociado al posterior consumo de alcohol y otras sustancias, lo cual no se aparta de lo hallado en otros trabajos 10,20 . Según los diferentes tipos de conflictos familiares analizados en los delincuentes por violencia de género, hemos podido observar que el alcoholismo paterno es el que guarda una mayor relación con el posterior consumo de alcohol y otras sustancias.…”
Section: Discussionunclassified
“…Además, un elevado nivel de conflicto parental puede transmitirse como un modelo negativo para el manejo de las relaciones, desarrollando peores habilidades de enfrentamiento a los conflictos de pareja 28 . Una mayor exposición al conflicto parental en la niñez, se asocia, en la adolescencia y adultez, con parejas que terminan su relación más rápido, tienen relaciones insatisfactorias y mayor violencia dentro de la pareja 22,[29][30][31] . El conflicto parental tiene mayor impacto en las conductas sexuales de riesgo en los hijos que el divorcio de los padres 32 .…”
Section: Consecuencias a Largo Plazo En El Plano Afectivo De La Discounclassified